Inline and Sideline Approaches for Low-cost Memory Safety in C - Nam, Myoung Jin (Apollo - University of Cambridge Repository, 2020)
System languages such as C or C++ are widely used for their high performance, however the allowance of arbitrary pointer arithmetic and type cast introduces a risk of memory corruptions. These memory errors cause unexpected termination of programs, or even worse, attackers can exploit them to alter the behavior of programs or leak crucial data. Despite advances in memory safety solutions, high and unpredictable overhead remains a major challenge. Accepting that it is extremely difficult to achieve complete memory safety with the performance level suitable for production deployment, researchers attempt to strike a balance between performance, detection coverage, interoperability, precision, and detection timing. Some properties are much more desirable, e.g. the interoperability with pre-compiled libraries. Comparatively less critical properties are sacrificed for performance, for example, tolerating longer detection delay or narrowing down detection coverage by performing approximate or probabilistic checking or detecting only certain errors. Modern solutions compete for performance. The performance matrix of memory safety solutions have two major assessment criteria – run-time and memory overheads. Researchers trade-off and balance performance metrics depending on its purpose or placement. Many of them tolerate the increase in memory use for better speed, since memory safety enforcement is more desirable for troubleshooting or testing during development, where a memory resource is not the main issue. Run-time overhead, considered more critical, is impacted by cache misses, dynamic instructions, DRAM row activations, branch predictions and other factors. This research proposes, implements, and evaluates MIU: Memory Integrity Utilities containing three solutions – MemPatrol, FRAMER and spaceMiu. MIU suggests new techniques for practical deployment of memory safety by exploiting free resources with the following focuses: (1) achieving memory safety with overhead < 1% by using concurrency and trading off prompt detection and coverage; but yet providing eventual detection by a monitor isolation design of an in-register monitor process and the use of AES instructions (2) complete memory safety with near-zero false negatives focusing on eliminating overhead, that hardware support cannot resolve, by using a new tagged-pointer representation utilising the top unused bits of a pointer.
Keywords: Cyber security; Software security